Online dental management system - Khoo, Kok Hong (2014)
With the advancement of information technology, the use of information and communication technology has covered every aspects of the life. However, in Malaysia there are some dental clinics are still using the manually managing their records. The manual record management method can caused a lot of problems in the management process such as time wasting, lack of efficiency and so on, thus there is a need to replace it into the computerized management system as computerized management system can solve the problems that are always encounter by the manual record management method to make the daily operation of the dental clinics more easier and effectively. In this project, beside using Hypertext Preprocessor (PHP) as the main programming language in developing the system, some open source web technologies such as Hypertext Markup Language 5 (HTML5), Cascading Style Sheets (CSS) and JavaScript (JS) are also implemented which enhances the functionality and usability of this web based application. In short, this project will help to improve the daily clinic operation of my client which is CHOO Specialist Orthodontic & Dental Clinic as well as cutting down some operational costs.